Reinforced Concrete Durability Design Through a Semi-probabilistic Approach - Sundhar Paulpandian, Murali Kannan; Neves, Rui (Periodica Polytechnica Civil Engineering, 2023)
This study provides a semi-probabilistic approach to durability design of reinforced concrete structures, subjected to carbonation-induced corrosion. The method was developed from an existing approach and using comprehensive data collated from the literature. A statistical model for predicting accelerated carbonation coefficient, using as input variables mix proportions and test conditions was also generated. The performance of the proposed method was assessed and proved appropriate. Besides delivering a more consistent semi-probabilistic method to design for the avoidance of unforeseen carbonation-induced corrosion problems, the developed statistical model to estimate the accelerated carbonation coefficient is a useful tool on the mix design, from the standpoint of conforming with the accelerated carbonation coefficients obtained through the semi-probabilistic method.